GAMBARAN RINITIS ALERGI PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS RIAU ANGKATAN 2013-2014 - Muhammad Rafi; Asmawati Adnan; Huriatul Masdar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAllergic Rhinitis is an inflammation reaction at nasal mucous that is caused by allergic reaction mediated by IgE, its identified by symptoms like rinore, sneeze, nasal itch, nasal congestion, itchy and watery red eyes. This research was done to visualizing and evaluating allergic rhinitis among stundents of Riau University’s Medical Faculty Generation 2013/2014. The design of the research was desciptive research wih cross sectional approach using total sampling sample recovery technique. From 293 respondents, 74 was suspected to having allergic rhinitis based from their questioner, physical examination, and skin prick test. From the result of the research, prevalention of allergic rhinitis is 74 students (25.25%). Further description of the research revealed that gender with the most allergic rhinitis suspect is female (19,79%), the most complained symptom is sneeze (03,24%), followed by nasal congestion (85,13%), the most common classification of allergic rhinitis to be the intermitten type (64,86%), the most common degree of allergic rhinitis is moderate-severe (50%). On physical inspection, allergic shiner (86,48%) is the most common physical findings, findings from anterior rhinoscope examination is livid mucous (100%). Tyoe of aeroallergen most commonly found is Dermatophagoides farinae (63,51%) followed by Dermatophagoides pteronyssinus (60,81%) and Blomia Tropicalis (58,10%)Key words : Allergic Rhinits, Nasal mucous inflammation, Skin Prick Test, aeroallergen.